A deep Chandra survey for faint X-ray sources in the Galactic globular cluster M30, and searches for optical and radio counterparts. Issue 3 (25th September 2020) - Zhao, Yue; Heinke, Craig O; Cohn, Haldan N; Lugger, Phyllis M; Guillot, Sebastien; Echiburú, Constanza; Shishkovsky, Laura; Strader, Jay; Chomiuk, Laura; Bahramian, Arash; Miller-Jones, James C A; Maccarone, Thomas J; et al.
ABSTRACT: We present a deep (∼330 ks) Chandra survey of the Galactic globular cluster M30 (NGC 7099). Combining the new Cycle 18 with the previous Cycle 3 observations we report a total of 10 new X-ray point sources within the 1${_{.}^{′}}$ 03 half-light radius, compiling an extended X-ray catalogue of a total of 23 sources. We incorporate imaging observations by the Hubble Space Telescope and the Karl G. Jansky Very Large Array from the MAVERIC survey to search for optical and radio counterparts to the new and old sources. Two X-ray sources are found to have a radio counterpart, including the known millisecond pulsar PSR J2140−2310A, the radio position of which also matches a previously reported faint optical counterpart which is slightly redder than the main sequence. We found optical counterparts to 18 of the 23 X-ray sources, identifying two new cataclysmic variables (CVs), five new CV candidates, two new candidates of RS CVn type of active binary (AB), and two new candidates of BY Dra type of AB. The remaining unclassified X-ray sources are likely background active galactic nuclei (AGNs), as their number is consistent with the expected number of AGN at our X-ray sensitivity. Finally, our analysis of radial profiles of different source classes suggests that bright CVs are more centrally distributed than faint CVs in M30, consistent with other core-collapsed globular clusters.